已知函数f(x)=a^(x^2+3x-4),g(x)=a^(x^2+2x-2) (a>0,a≠1),若f(x)>g(x)
1个回答
f(x)>g(x)
a^(x^2+3x-4)>a^(x^2+2x-2)
若0
相关问题
已知函数f(x)=2x+a,g(x)=1/4(x^2+3)若g[f(x)]=x^2+x+1,求a的值
已知函数f(x)=a-2/(2^x+1),g(x)=1/(f(x)-a) 若g(2x)-a*g(x)=0有唯一实数解求a
已知函数f(x)= 1 2 x 2 -2x+2,g(x)=lo g a 1 x (a>0,且a≠1) ,函数h(x)=f
已知f(x)=2x+a,g(x)=[1/4](x2+3),若g(f(x))=x2+x+1,求a的值.
已知f(X)=2X+a,g(X)=1/4(X^2+3),若g[f(X)]=X^2+X+1,求a的值
已知函数f(x)=(4x)/(3x^2+3),函数g(x)=1/3*a*x^3-a^2*x,x∈【0,2】
函数f(x)=a^2x^2-3X+1,g(x)=a^x^2+2x-5(a>0,a≠1),若f(x)>g(x),求x的取值
已知函数f(x)=x^3-ax^2-a^2x+1 g(x)=1-4x-ax^2其中实数a≠0 若f(x)与g(x)在区间
已知函数f(x)=lnx,g(x)=(2a²)/(x²) (a>0),设F(x)=f(x)+g(x)
已知实数a>0,函数f(x)=x2-ax-2a-b,g(x)=a2lnx-(a2+a)lna,F(x)=f(x)-g(x